Exploring thankfulness: a study of linguistic choices in postgraduate thesis acknowledgements - Nur Zafirah Razali (Pusat Penataran Ilmu dan Bahasa,Universiti Malaysia Sabah, 2024)
The acknowledgement page of a postgraduate thesis is a special space where postgraduate students express their gratitude and thankfulness prior to completing their studies. The present study delves into gratitude expressions through an analysis of the linguistic choices employed by Malaysian postgraduate students in their thesis acknowledgements when conveying appreciation. Accordingly, by examining a diverse range of linguistic choices in the acknowledgement page, this study seeks to uncover patterns, variations, and nuances in how gratitude is articulated within the academic context as well as how language is used to convey gratitude. In addition, through a meticulous examination of linguistic strategies such as lexical choices and rhetorical devices from the pragmatics perspective, this qualitative study further sheds light on the intricacies of expressing thankfulness in academic writing, including theses and dissertations. The findings of this study contribute to a deeper understanding of the role of language in conveying gratitude, offering insights that may benefit both academic writers and readers in the realm of postgraduate research. Furthermore, besides uncovering the cultural, social, and personal factors that drive gratitude expressions, this study also adds to the understanding of gratitude communication in academia and provides valuable implications for academic writing practices and interpersonal relationships within scholarly communities.